The C-C Chemokine Receptor Type 4 Is an Immunomodulatory Target of Hydroxychloroquine - Beck, Tyler C.; Beck, Kyle R.; Holloway, Calvin B.; Hemings, Richard A.; Dix, Thomas A.; Norris, Russell A. (Frontiers in Pharmacology, 2020)
The emergence of ​a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; COVID-19) in China, reported to the World Health Organization on December ​31st, 2019, has led to a large global pandemic and is a major public health issue. As a result, there are more than 200 clinical trials of COVID-19 treatments or vaccines that are either ongoing or recruiting patients. One potential therapy that has garnered international attention is hydroxychloroquine; a potent immunomodulatory agent FDA-approved for the treatment of numerous inflammatory and autoimmune conditions, including malaria, lupus, and rheumatoid arthritis. Hydroxychloroquine has demonstrated promise in vitro and is currently under investigation in clinical trials for the treatment of COVID-19. Despite an abundance of empirical data, the mechanism(s) involved in the immunomodulatory activity of hydroxychloroquine have not been characterized. Using the unbiased chemical similarity ensemble approach (SEA), we identified C-C chemokine receptor type 4 (CXCR4) as an immunomodulatory target of hydroxychloroquine. The crystal structure of CXCR4 was selected for molecular docking studies using the SwissDock modeling software. In silico, hydroxychloroquine interacts with GLY-159 within the CXCR4 active site, presumably blocking endogenous ligand binding. However, the FDA-approved CXCR4 antagonist plerixafor outperformed hydroxychloroquine in silico, demonstrating energetically favorable binding characteristics. Hydroxychloroquine may subject COVID-19 patients to QT-prolongation, increasing the risk of sudden cardiac death. Plerixafor is not known to increase the risk of QT prolongation and may serve as a viable alternative to hydroxychloroquine. Results from this report introduce additional FDA-approved drugs that warrant investigation for therapeutic use in the treatment of COVID-19.